ANALISIS STRATEGI BISNIS DAN PELUANG PASAR WARUNG KOPI DUREN: INOVASI RASA DALAM INDUSTRI KULINER - Muhamad Sofyan Sanusi; Dhimas Raihan Asshidiq; Jose Emmanuel Haris; Muhammad Rizal Ardiansyah; Rifki Ramdika (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the development strategy of Warung Kopi Duren MSMEs to enhance its business progress using a qualitative method with internal analysis, including SWOT, operational and financial conditions, as well as external analysis using PESTEL and Porter's Five Forces. Data were collected through observations and interviews. The results show that affordable product prices and independent management of durian raw materials, ensuring product quality and cost efficiency, are key advantages. However, challenges such as a less strategic location, ineffective marketing strategies, and underutilization of market opportunities are major obstacles. Recommendations include strengthening digital promotion, collaborating with influencers, diversifying the menu, improving social media platforms, and enhancing human resources quality through regular evaluations and workshops for management and staff involved in Warung Kopi Duren on the importance of understanding the market and business knowledge in a broader sense. These findings are expected to serve as a reference for similar culinary businesses in developing sustainable business strategies.